Chemical synthesis of nanocrystalline Ni-Zn ferrites and their magnetic characteristics - Jong-Chul Lee; Joon-Hyung Lee; Jeong-Joo Kim; Golub, V.; Sang-Hee Cho; O`Connor, C.J.; Caruntu, D.; Cushing, B. (Functional Materials, 2006)
Nanocrystalline Ni₁₋ₓZnₓFe₂O₄ powders were synthesized by the citrate precursor method, and the reaction sequence during the process was examiden. Studied of the reaction sequence showed that a NiFe2O4 phase was developed as soon as the metal citric acids were thermally decomposed. In the case of ZnFe₂O₄, however, ZnO and Fe₂O₃ were produced first when the metal citric acids were decomposed at low temperature. A single phase of ZnFe₂O₄ was subsequently obtained when a heat treatment was conducted at 500°C for 2 h. On the other hand, in order to examine the effect of particle size on magnetic characteristics of Ni-Zn ferrites, nanocrystalline Ni₁₋ₓZnₓFe₂O₄ powders with particle sizes of approximately 7, 25 and 100 nm were prepared by coprecipitation and citrate precursor methods. The magnetic characteristics of the ultrafine (7 nm) and coarse (100 nm) nanocrystalline ferrites showed differences. These differences are attributed to cation disordering at the surfaces of particles, wich becomes increasingly dominant as the particle size decreases.